ANALISIS PERMASALAHAN GURU TERKAIT PERENCANAAN DAN PELAKSANAAN PERANGKAT PEMBELAJARAN BIOLOGI MELALUI MODEL PROBLEM BASED LEARNING DAN MEDIA REALITA DI SMA - Fitri Andayani; Makrina Tindangen; Zeni Haryanto (Pascasarjana Universitas Negeri Malang, 2017)
The purpose of this study is to obtain (1) understanding of high school teachers related to the planning and implementation of learning tools with learning model Problem Based Learning and media reality, (2) display of teacher problems related to the implementation of high school teachers related to learning tools with Problem Based Learning model and reality media, (3) description of student's problem to result of learning on environmental pollution material. The result of observation of teacher and student problem analyzed by qualitative descriptive indicate that teacher's understanding related to Biology based learning model of Problem Based Learning and Media Reality is still very low so that its use in the learning process has not been running optimally, the teacher experiences obstacles in making learning tools include syllabus, RPP, Hand Out, and LKPD. Assessment shows a low percentage or less so that student learning outcomes are also low. Therefore it is necessary to develop biology learning tools with problem-based learning model and reality media to improve student learning outcomes. Tujuan penelitian ini adalah untuk memperoleh (1) gambaran pemahaman guru SMA terkait perencanaan dan pelaksanaan perangkat pembelajaran dengan model pembelajaran Problem Based Learning dan media realita, (2) gambaran permasalahan guru terkait pelaksanaan guru SMA terkait perangkat pembelajaran dengan model Problem Based Learning dan media realita, (3) gambaran permasalahan siswa terhadap hasil belajar pada materi pencemaran lingkungan. Hasil observasi permasalahan guru dan siswa yang dianalisis secara deskriftif kualitatif menunjukkan bahwa pemahaman guru terkait perangkat pembelajaran Biologi berbasis model Problem Based Learning dan Media Realita masih sangat rendah sehingga penggunaannya pada proses pembelajaran belum berjalan secara optimal, guru mengalami kendala dalam pembuatan perangkat pembelajaran meliputi silabus, RPP, handout, dan LKPD. Penilaian menunjukan persentase yang rendah atau kurang sehingga hasil belajar siswa juga rendah. Oleh karena itu, diperlukan pengembangkan perangkat Pembelajaran Biologi dengan model pembelajaran berbasis masalah dan media realita untuk dapat meningkatkan hasil belajar siswa.